Review paperBidirectional inferior vena cava-pulmonary artery shunt: can it be an alternative for older patients presenting single ventricle heart disease in the third world countries? - Ugurlucan, Murat; Basaran, Murat; Alpagut, Ufuk; Tireli, Emin (Archives of Medical Science, 2008)
The single ventricle cardiac pathologies are commonly treated with total cavopulmonary anastomosis in the current era. The modality is usually performed in two stages and the bidirectional superior vena cava-pulmonary artery shunt constitutes the first stage; after a certain period, the inferior vena cava is connected to the anastomosis. However, especially in relatively older patients, single stage total cavopulmonary anastomosis is performed with various mortality and morbidity rates. This report is a review of an alternative method to the classical order of total cavopulmonary anastomosis, a prior bidirectional inferior vena cava-pulmonary artery shunt as a preparatory operation for total cavopulmonary connection in selected patient groups.